2017
DOI: 10.1016/j.genhosppsych.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

How changes in physical activity relate to fatigue interference, mood, and quality of life during treatment for non-metastatic breast cancer

Abstract: Objective Physical activity (PA) following surgery for breast cancer may improve depressive symptoms and quality of life (QoL) via reduction in fatigue-related daily interference (FRDI). Less is known about how change in PA may relate to these psychosocial factors throughout the course of treatment. In a secondary analysis of a previous psychosocial intervention trial, we examined relationships between change in PA, depressive symptoms, and functional QoL, as mediated by change in FRDI, and whether naturally o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 55 publications
4
16
0
1
Order By: Relevance
“…We have not found any study reporting the relationship between low physical activity and low quality of life among female pelvic cancer survivors suffering from fecal or urinary leakage. However, among breast cancer survivors, increased physical activity reduced clinician-rated depressed mood and improved quality of life [39]. Furthermore, practicing physical activity was related to reduce depressed mood in non-cancer general populations [40,41].…”
Section: Discussionmentioning
confidence: 96%
“…We have not found any study reporting the relationship between low physical activity and low quality of life among female pelvic cancer survivors suffering from fecal or urinary leakage. However, among breast cancer survivors, increased physical activity reduced clinician-rated depressed mood and improved quality of life [39]. Furthermore, practicing physical activity was related to reduce depressed mood in non-cancer general populations [40,41].…”
Section: Discussionmentioning
confidence: 96%
“…These interventions may operate on psychological predictors of pain (e.g., pain catastrophizing, symptom management self-efficacy) and promote adaptive coping. Likewise, increased physical activity has been shown to reduce pain and depressive symptoms, and enhance the functional quality of life via decreased fatigue-related interference (Fisher et al, 2017; Irwin et al, 2015). Although speculative, better management of pain symptoms after surgery may also mitigate pro-inflammatory processes which have been associated with depression on the one hand and poorer health outcomes on the other (Antoni & Dhabhar, 2019; Edwards et al, 2011; McGregor & Antoni, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed fewer cases of anxiety in the more physically active group, although the prevalence differences for anxiety did not reach statistical significance between groups. While a handful of trials report positive associations and effects of PA on mental health in cancer patients, 58,59 and that insufficient PA is associated with depression and anxiety, 60 more robust evidence from systematic reviews of randomized controlled trials reported mild or insignificant changes for depression and anxiety. 56,61,62 We found that perceived social support was superior among more active patients, although the difference between groups was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%